Nonautonomous multisoliton solutions of the 1D Gross-Pitaevskii equation with time-dependent coefficients - Pérez Riascos, Alejandro; Rugeles Pérez, Alvaro (Revista de Ciencias, 2014)
In this paper we investigate bright multisoliton solutions of the one-dimensional Gross-Pitaevskii equation with a parabolic potential, a time-dependent nonlinearity, and a term related to gain or loss. Analytical N-soliton solutions are obtained by using the relation between the Gross-Pitaevskii equation with time dependent coefficients and the standard nonlinear Schr¨odinger equation. In particular, we study interactions between snake solitons. Keywords: Gross-Pitaevskii equation, nonautonomous solitons. Resumen En este trabajo se estudian multisolitones brillantes de la ecuación de Gross-Pitaevskii con un potencial parab´olico, una no linealidad dependiente del tiempo y un término relacionado con ganancias o p´erdidas en un condensado. Se obtienen soluciones analíticas con N solitones utilizando la relación existente entre la ecuación de Gross-Pitaevskii con coeficientes dependientes del tiempo y la ecuación no lineal de Schr¨odinger. Se hace un estudio particular de los solitones serpiente y sus interacciones. Palabras Claves: Ecuación de Gross-Pitaevskii, solitones no autónomos.